Might Necrotic Keratinocytes Contribute to the Diagnosis and Pathogenesis of Psoriasis? - Bengu Cevirgen Cemil; Aysun Gokce; Gamze Taş Aygar; Selda Pelin Kartal (Mattioli1885, 2024)
Introduction: Psoriasis is a chronic inflammatory skin disease that can pose challenges in histopathological diagnosis. The diagnostic importance of necrotic keratinocytes has recently been emphasized. Necrotic keratinocytes refer to keratinocytes undergoing programmed cell death. It is increasingly evident that programmed cell death pathways play a significant role in the development and progression of psoriasis. Moreover, studies have revealed the involvement of programmed cell death mechanism called PANoptosis in the pathogenesis of psoriasis. Objectives: In this study, our objective was to investigate the significance of necrotic keratinocytes in both the diagnosis and pathogenesis of psoriasis. Methods: We analyzed the number of necrotic keratinocytes in 135 samples of psoriasis, 57 samples of psoriasiform spongiotic dermatitis, and 71 samples of normal skin. Additionally, we assessed the distribution of necrotic keratinocytes in the upper, middle, and lower thirds of the epidermis. Results: Our findings showed a significant difference in the total number of necrotic keratinocytes and their distribution among the epidermal regions between patients with psoriasis and both the psoriasiform spongiotic dermatitis and control groups (p<0.001). Specifically, necrotic keratinocytes were predominantly found in the upper epidermis (77.5%) in psoriasis cases. Furthermore, we observed a strong correlation between the Psoriasis Area and Severity Index (PASI) scores and the total count of necrotic keratinocytes in psoriasis patients (r = 0.72). Conclusions: Our study highlights the role of necrotic keratinocytes, resulting from programmed cell death, as important marker cells in both the diagnosis and pathogenesis of psoriasis.